Transformasi Model Bisnis dan Tantangan Ekosistem AI pada Startup Digital (2021–2026): Systematic Literature Review - Andiky Vicky Handayana Putra; Siska Fitriani; Younes Limoury; Ryan Randy Suryono (TIN: Terapan Informatika Nusantara, 2026)
As the adoption of Artificial Intelligence (AI) by digital startups increases, the existing literature remains fragmented between technical and managerial perspectives, making it difficult to comprehensively understand the role of AI in digital entrepreneurship. This study aims to systematically synthesize how AI affects value creation, operational strategies, and adoption challenges in various ecosystem contexts. Using the SLR method based on Kitchenham's guidelines, this study conducted a comprehensive search of reputable academic databases, namely Scopus and ScienceDirect. Through a rigorous quality assessment process to ensure data validity, 21 high-quality primary studies published between 2021 and 2026 were selected. The review results show that AI not only functions as a tool for increasing efficiency, but also as a strategic capability that drives the transformation of startup business models from static product offerings to predictive and dynamic personalized services. In addition, the role of AI evolves throughout the startup life cycle, from cognitive support at the ideation stage to the main mechanism that supports non-linear growth in the development phase. The study also identifies differences in AI adoption challenges, where ethical and regulatory issues are more prominent in developed countries, while talent and infrastructure limitations are major obstacles in developing countries. This research emphasizes the importance of viewing AI as a supporting capability that strengthens, rather than replaces, the role of entrepreneurs in building sustainable competitive advantage.